2014
DOI: 10.5902/1980509814563
|View full text |Cite
|
Sign up to set email alerts
|

Eficiência do uso da radiação solar por plantas <i>Ilex paraguariensis</i> A. St. Hil. cultivadas sob sombreamento e a pleno sol

Abstract: RESUMOA eficiência de conversão da radiação solar em fitomassa é uma variável frequentemente utilizada em modelos de simulação do crescimento das culturas, pois a produção de biomassa está relacionada com a eficiência com que uma planta converte energia radiante em química, dada pelo processo da fotossíntese. Dessa maneira, o objetivo deste trabalho foi determinar a eficiência de conversão da radiação solar fotossinteticamente ativa interceptada (RFAi) em fitomassa aérea de Ilex paraguariensis, cultivada em co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 4 publications
4
18
0
2
Order By: Relevance
“…With the higher seedling density in the trays, the accumulated TDM presented an increase in values, according to Ataíde et al (2010) and Caron et al (2014). The major accumulation of dry matter, obtained as a function of days after emergence in the treatment of high density, is associated to LAI.…”
Section: The Interception Of Solar Radiation Is Increased With the Inmentioning
confidence: 60%
See 2 more Smart Citations
“…With the higher seedling density in the trays, the accumulated TDM presented an increase in values, according to Ataíde et al (2010) and Caron et al (2014). The major accumulation of dry matter, obtained as a function of days after emergence in the treatment of high density, is associated to LAI.…”
Section: The Interception Of Solar Radiation Is Increased With the Inmentioning
confidence: 60%
“…Thus, the intercepted photosynthetically active radiation (PARi) that is converted into biomass, reveals the efficiency of the use of radiation (εb) by species (Monteith, 1977). In most cases, this process presents a linear function, as observed in the works developed by Stape et al (2008); Campoe et al (2013);Caron et al (2014), among others. One of the factors that is known to influence the εb is the leaf area index (LAI), a characteristic that can be modified by the density of seedlings.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…This result can be supplemented by Caron et al (2013), who found this behavior in the yerba mate associated with Pinus elliottii, and also by Sinclair et al (1992), who observed, for corn and soybean, that the increased diffuse radiation fraction resulted in more efficient use of radiation by the crops. This behavior may have been responsible for the significant difference among treatments with and without the application of the growth reducer, from dose of 120 kg ha -1 of N.…”
Section: Resultsmentioning
confidence: 77%
“…Considering the several aspects related to the improvement of the species, the effect of nutritional status of different provenances (OLIVA et al, 2014) and their respective progenies (STURION; RESENDE, 2005;RAKOCEVIC et al, 2005), the sexual dimorphism (male and female plants, (RAKOCEVIC et al, 2011;RESENDE, 2010), the cultivation system (in consortium or homogenous) (CARON et al, 2014) and the cultivation type have showed a strong influence on leaf mass production (RAKOCEVIC et al, 2007;2009). In a similar way, some morphological variations, mainly related to leaves (BASTOS et al, 2014;BORILLE et al, 2005;VALDUGA et al, 2016) were described in Brazil (REISSMANN et al, 2003) and Argentina (JANSSENS;SCHERER, 2011), however, they were not still linked to the productivity of the species.…”
Section: Introductionmentioning
confidence: 99%